EFEKTIFITAS PENERAPAN STRATEGI PEMBELAJARAN QUANTUM TEACHING DALAM TATANAN KOOPERATIF TIPE STAD PADA PEMBELAJARAN MATEMATIKA KELAS VIII-2 SMPN 29 PEKANBARU - Ritonga, Zulfan (Jurnal Pilar Sains, 2007)
The purpose of this research is to improve the effectiveness of learning through the application oflearning strategies in the teaching of quantum order type STAD cooperative learning. Implementation ofthis strategy refers to (1) determination of the action plan; (2) the actions of the application of quantumteaching strategies in order STAD cooperative type, (3) observation of teacher and student activities, and(4) to reflect on the effectiveness of implementation strategies learning. This course consists of two cyclesof meetings 3 times per cycle. The data collected in this study is the observation and data on learningoutcomes. Data on teacher and student activities, and classroom atmosphere using observation sheets andquestionnaires. While studying the results of data obtained through daily tests test each completed onecycle. Data analysis used descriptive statistical analysis. Based on research results during the cycle I andcycle II shows the effectiveness of the application of teaching learning strategies in order quantumcooperative learning can improve teacher and student activities, improve student learning outcomes, andclassroom atmosphere for the better.Keywords: Effectiveness, Quantum Teaching, Learning Cooperative Type STAD